Gliomatosis Cerebri: Current Understanding and Controversies - Ranjan, Surabhi; Warren, Katherine E. (Frontiers in Oncology, 2017)
Gliomatosis cerebri is a rare, extensively infiltrating glioma involving multiple contiguous lobes of the brain. This lethal disease affects all age groups and the majority of patients have a poor outcome despite aggressive treatment. Despite its initial recognition in 1938, gliomatosis cerebri remains a controversial entity with little consensus in its definition, histology or treatment. The majority of gliomatosis cerebri tumors are astrocytic, although mixed phenotypes have been identified. Treatment of gliomatosis cerebri is challenging as surgery is generally not an option due to the extensive areas of brain involved, the benefit of radiation therapy is unclear, and no chemotherapy has proven efficacy. Due to the rarity of the disease and its heterogeneity, both at histopathological and molecular levels, it is difficult to conduct clinical trials tailored for this diagnosis. This review summarizes our current knowledge, examines clinical studies focusing on the treatment of gliomatosis cerebri, highlights ongoing challenges, and discusses the recent molecular insights into adult and pediatric gliomatosis cerebri. We conclude that, although no longer recognized as a distinct pathological entity, gliomatosis cerebri represents a unique disease phenotype. Given the histologic and molecular overlap with other diffuse gliomas, the research emphasis should be on investigating its unique invasive biology.